Financial Deepening on Sharia Finance Perspective: Analysis in Indonesia and Malaysia - Kurniawati Meylianingrum; Tiara Juliana Jaya; Kholilah Kholilah; Mariam Ait Ahmed (Sharia Economic and Management Business Journal (SEMBJ), 2026)
This study examines the dynamic relationship between the Islamic financial sector and financial deepening in Indonesia and Malaysia by integrating two key components of the sharia financial system: the sharia capital market and Islamic banking. Using monthly pooled data from 2014-2024 and employing the Autoregressive Distributed Lag approach, the research investigates both short-term and long-term effects of corporate sukuk, sharia stocks, third-party funds, total assets, interest rates, and exchange rates on financial deepening. The findings reveal that corporate sukuk exert a negative influence on financial deepening in the short run, primarily due to their illiquidity and dominance by institutional buy-and-hold investors, while showing no significant long-term effect in either country. Sharia stocks positively affect financial deepening only in the short run, whereas long-term effects remain insignificant because of market volatility, limited liquidity, and structural constraints within the sharia capital market. Third-party funds demonstrate a contrasting pattern, showing negative short-run effects but a strong and positive long-run impact, indicating their growing role in supporting Islamic banking intermediation. Total asset contributes positively to financial deepening in the short term; however, their long-term effect becomes negative, reflecting inefficiency in translating asset growth into real-sector financing. Robustness test using Malaysia support the main model’s conclusion. The study underscores the importance of enhancing liquidity, strengthening intermediation efficiency, and improving cross-sector sharia financial integration to maximize the contribution of Islamic finance toward sustainable financial deepening in dual banking systems.